Perception of social media credibility and online political participation by young adults in Ibadan metropolis, Nigeria (2019)
This study was carried out to determine the perception of social media credibility and online political participation among young adults in Ibadan Metropolis. This study was guided by the Elaboration Likelihood Model (ELM). Mixed research method was used as the research design (survey and focus group discussion). The study employed multi-stage sampling technique to select (n=289 for the survey; n=40 for FGDs) respondents and discussants respectively for the study. Questionnaire and focus group discussion guide were used as research instruments. Results revealed that interactivity, accessibility from medium dimension and accuracy, objectivity from message dimension are the main determinants of social media credibility. Furthermore, results also showed that there is a significant relationship between perceived credibility of social media and online political participation among young adults. Thus, it was recommended, among others, that political actors should utilise this platform for online mobilisation of this cohort.